Neutrophil-to-Lymphocyte and Platelet-to-Lymphocyte Ratios as Predictors of Outcomes in Patients With Unresectable Hepatocellular Carcinoma Undergoing Transarterial Chemoembolization Plus Sorafenib - Zhang, Lei; Yan, Zhi-Ping; Hou, Zhong-Heng; Huang, Peng; Yang, Min-Jie; Zhang, Shuai; Zhang, Shen; Zhang, Shao-Hua; Zhu, Xiao-Li; Ni, Cai-Fang; Li, Qiang (Frontiers in Molecular Biosciences, 2021)
Objectives: To investigate the predictive value of inflammatory biomarkers in patients with unresectable hepatocellular carcinoma (HCC) for outcomes following the combining treatment of transarterial chemoembolization (TACE) plus sorafenib. Materials and Methods: A total of 314 (270 male and 44 female) treatment-naïve patients with unresectable HCC treated by TACE plus sorafenib between January, 2011 and December, 2018 were enrolled in the retrospective study. The primary outcome was overall survival (OS). The secondary outcome was progression-free survival (PFS). Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) were obtained within 3-7 days before the initial TACE and the median value of the NLR and PLR was considered as the cut-off value. Results: The median value of NLR and PLR was 2.42 and 100, respectively. The median OS and PFS of the entire cohort were 18.7 months (95%CI: 16.8-20.6) and 9.1 months (95%CI: 8.5-9.8), respectively. The low NLR and PLR group showed improved OS and PFS compared with the high NLR and PLR group (21.8 months (95% CI: 15.2-28.5) vs. 15.4 months (95% CI: 12.4-18.3), P<0.0001; 21.6 months (95%CI: 15.8-27.5) vs. 14.9 months (95%CI: 11.9-17.8), P=0.00027; respectively). In addition, the low NLR and PLR group also provided a longer PFS than the high NLR and PLR group (10.4 months (95% CI:8.9-12.0) vs. 8.1 months (95% CI:7.1-9.2), P=0.00022; 10.3 months (95% CI:8.6-11.9) vs. 8.2 months (95% CI:7.2-9.2), P<0.0001; respectively). High NLR and PLR at baseline were predictive factors of poor OS (P=0.02 and P=0.004) and PFS (P=0.045 and P=0.005). Conclusion: This study showed the prognostic value of quantitative inflammatory biomarkers in correlation with OS and PFS in unresectable HCC patients undergoing TACE plus sorafenib treatment.